2005
DOI: 10.1007/s00439-005-1273-4
|View full text |Cite
|
Sign up to set email alerts
|

De novo t(7;10)(q33;q23) translocation and closely juxtaposed microdeletion in a patient with macrocephaly and developmental delay

Abstract: We have applied FISH with fully integrated BACs and BAC subfragments assessed in the human genome sequence to a de novo t(7;10)(q33;q23) translocation in a patient with developmental delay and macrocephaly. The translocation breakpoints disrupt the SEC8L1 gene on chromosome 7 and the PTEN gene on chromosome 10. RT-PCR demonstrated chimeric transcripts containing the first 11 exons of SEC8L1 fused to exon 3 of PTEN. In addition to the balanced translocation, we found a 7-Mb deletion in the translocated part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Liu et al have already noted the PI3-kinase-and AKT-independent effects of nuclear-targeted PTEN, although they found PTEN phosphatase activity to be required for G1 arrest and for inhibition of soft agar growth . Additional mechanisms underlying PTEN alterations have also just been uncovered, including promoter mutations in GBM (Tunca et al, 2007), translocations in thyroid cancer (Puxeddu et al, 2005) and Cowden syndrome (CS)-like disease (Yue et al, 2005), and splicing mutations in Bannayan-RileyRuvalcaba syndromes (BRRS) (Suphapeetiporn et al, 2006), CS (Agrawal et al, 2005) and sporadic breast cancers (Agrawal and Eng, 2006). Furthermore, a micro-RNA that could target PTEN (miR-21) has been shown to be highly expressed in human cholangiocarcinoma cell lines (Meng et al, 2006) and hepatocellular carcinoma (Meng et al, 2007).…”
mentioning
confidence: 99%
“…Liu et al have already noted the PI3-kinase-and AKT-independent effects of nuclear-targeted PTEN, although they found PTEN phosphatase activity to be required for G1 arrest and for inhibition of soft agar growth . Additional mechanisms underlying PTEN alterations have also just been uncovered, including promoter mutations in GBM (Tunca et al, 2007), translocations in thyroid cancer (Puxeddu et al, 2005) and Cowden syndrome (CS)-like disease (Yue et al, 2005), and splicing mutations in Bannayan-RileyRuvalcaba syndromes (BRRS) (Suphapeetiporn et al, 2006), CS (Agrawal et al, 2005) and sporadic breast cancers (Agrawal and Eng, 2006). Furthermore, a micro-RNA that could target PTEN (miR-21) has been shown to be highly expressed in human cholangiocarcinoma cell lines (Meng et al, 2006) and hepatocellular carcinoma (Meng et al, 2007).…”
mentioning
confidence: 99%
“…Amplification of larger (10 -15 kb) BAC subfragments was carried out with a series of primer pairs (Table 2) chosen from the genomic sequence of BAC RP11-463M16, as described previously. 13,14 Genomic BAC DNAs and their long-range PCR products were labeled with biotin-16-dUTP or digoxigenin-11-dUTP (Roche) by standard nick translation and FISH mapped on metaphase chromosomes. 15 …”
Section: Classical and Molecular Cytogenetic Techniquesmentioning
confidence: 99%
“…The fact that this SNP was found in the normally hearing father and paternal grandfather of our proband also argues against a dominant causative mutation, although the formal possibility of reduced penetrance in unaffected family members cannot be excluded. In some cases of apparently balanced chromosome rearrangements, microdeletions and/or duplications in the vicinity of the breakpoint regions [Yue et al, 2005] or elsewhere in the genome [Baptista et al, 2008] were found to be disease-causing. The SNP array analysis did not reveal any cryptic gain or loss of chromosome material in the proband (data not shown).…”
Section: Targeted Next Generation Sequencing Of Deafness Genes and Snmentioning
confidence: 99%